PENGARUH KEPEMIMPINAN, MOTIVASI KERJA, KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk UNIT PADANG BULAN - M. Irfan Sinulingga (JRMB (Jurnal Riset Manajemen & Bisnis), 2020)
The purpose of this research was to determine the effect of leadership on employee job satisfaction at Bank Rakyat Indonesia (Persero) Tbk Unit Padang Bulan. To determine the effect of work motivation on employee job satisfaction at Bank Rakyat Indonesia (Persero) Tbk Unit Padang Bulan. To determine the effect of organizational commitment on employee job satisfaction at Bank Rakyat Indonesia (Persero) Tbk Unit Padang Bulan. To determine the effect of leadership on employee performance at the Bank Rakyat Indonesia (Persero) Tbk Unit Padang Bulan. To determine the effect of work motivation on employee performance at Bank Rakyat Indonesia (Persero) Tbk Unit Padang BulanThe sample in this research amounted to 31 employees. Data analysis technique used in this research is multiple linear regression analysis.The research result of this research explain that leadership has a positive and significant effect on employee job satisfaction. Work motivation has a positive and significant effect on job satisfaction. organizational commitment has a positive and significant effect on job satisfaction. Leadership has a negative and not significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Organizational commitment has a positive and not significant effect on employee performance. Job satisfaction has a positive and not significant effect on employee performance.